Management Accountant Practice in Malaysian Public Sector - Yasmiza, Long; Ariza, Ibrahim; Syamsul Azri, Abdul Rahman; Ummi Junaidda, Hashim; Jamalludin Helmi, Hashim (2016)
Purpose - This study attempts to examine and analyse the roles of management accountant in Malaysian public sector. The current study has been embarked due to limitation of literature focussing on management accountant in the public sector. Two objectives have been identified; (1) to determine the task that most performed by the management accountant in Malaysian public sector, and (2) to analyse skills that most needed by management accountant. Design/methodology/approach - Questionnaires were distributed to Chartered Accountants attached with public sector department located in the East Coast of Malaysia. Findings - Results of the study show that the reporting, budgeting, financial accounting and strategic management accounting are the top four ‘tasks’ performed by management accountant in Malaysian public sector. It also reveals that the ability to work in group, and dare to take responsibility is the most important skills highly required by management accountant in Malaysian public sector. Research limitations/implications - This study contributes to the literature of management accounting by determining the most tasks and skill practiced by management accountant in Malaysian public sector. Originality/value - Keywords Management accountant; public sector. Paper Type Research paper